Antepartum Antibiotic Therapy under 34 Weeks of Gestation and Its Impact on Early-Onset Neonatal Infection and Maternal Vaginal Microbiota - Junsuke Muraoka; Masatoki Kaneko; Koutaro Doi; Yuki Kodama; Hiroshi Sameshima (Microbiology Research, 2022)
The use of prenatal antibiotics should be carefully considered, owing to their potential adverse effects on neonatal outcomes. This study aimed to identify the contributing factors to early-onset neonatal infection and to determine the influence of antepartum antibiotics on women and neonates. This study included 127 pregnant women without obvious intra-amniotic infection on admission, who delivered under 34 weeks of gestation. Information on maternal and neonatal characteristics was obtained from their medical charts. Vaginal swabs were taken from all women on admission. In total, 29 (22.8%) neonates developed early-onset infection. Multivariate analysis revealed that antepartum antibiotics were the most strongly associated factor for early-onset neonatal infection (odds ratio, 11.2; 95% confidence interval, 4.08–31.02). The frequency of early-onset neonatal infection was significantly higher in women who received antibiotic therapy than in those who did not; no significant difference in prolonging their gestation or neonatal morbidities was observed. The prevalence of women who hosted vaginal microorganisms on admission was similar to that in women whose infants subsequently developed early-onset neonatal infection compared with that of women whose infants did not. Among infants of the 40 women who received antepartum antibiotic therapy, 21 developed early-onset infection. Of the women who delivered these 21 infants, 62% (13/21) showed reduced lactobacilli and 43% (9/21) had resistant bacterial strains in their vaginal microbiota at the time of delivery. The use of antepartum antibiotics is the most strongly associated factor in early-onset neonatal infection; it does not prolong gestation and would change the vaginal environment.